STRATEGI PENDIDIKAN ISLAM DI TENGAH ARUS MODERNITAS : INTEGRASI ILMU KEISLAMAN DENGAN KOMPETENSI ABAD KE- 21 - Misbahul Munir, Misbahul Munir (STAI Al-Hidayat Lasem, 2025)
Modernity and globalization have brought fundamental changes to various aspects of life, including Islamic education. The main challenge faced is how the Islamic education system can produce graduates who are intellectually and professionally competent, while also solid in their Islamic identity and values amidst the rapid flow of global information and culture. This study aims to identify and analyze adaptive and transformational strategies in Islamic education to address the challenges of modernity. The method used is a literature review (library research) with a descriptive-analytical approach, examining various journals, books, and related scientific sources. The results indicate that effective strategies center on three main pillars: curriculum integration, strengthening technology-based adaptive pedagogy, and developing educator professionalism. Implementing these strategies is crucial to ensure the relevance and sustainability of Islamic education in producing a generation of globally competitive Muslims without losing its spiritual essence